Eco-Theology in Islamic Thought: Religious Moderation and Organizational Roles in Mining Management in Indonesia - Taufik Hidayatulloh; Ahmad Sunawari Long; Irawan; Theguh Saumantri (Progresiva : Jurnal Pemikiran dan Pendidikan Islam, 2024)
With the increasing irresponsible exploitation of natural resources, environmental damage has become increasingly concerning, particularly in the mining sector, which has a broad impact on ecosystems and the livelihoods of surrounding communities. The environmental crisis caused by mining activities in Indonesia demands a new approach to more sustainable resource management. This study aims to explore the role of religious moderation from the perspective of eco-theology, which has the potential to offer solutions for natural resource management. Eco-theology provides spiritual principles that can be integrated into environmental policies, creating a balance between economic interests, ecology, and societal well-being. This research is a literature review employing a descriptive analysis method. The results show that eco-theology offers a relevant framework for shifting the paradigm of mining management from anthropocentrism to ecocentrism. Religious organizations have great potential to promote sustainable mining management by incorporating spiritual values into environmental practices. Religious moderation serves as a foundational pillar in strengthening ecological awareness, improving the relationship between humans and nature, and encouraging sustainable development aligned with religious principles.